Evaluation of Competency-Based Medical Education (CBME) curriculum implementation for Phase II Medical undergraduates: A qualitative study - KRISHNAMURTHY SOUNDARIYA; ANANDABASKAR NISHANTHI; RAJALAKSHMI MAHENDRAN; MOUROUGUESSINE VIMAL (Journal of Advances in Medical Education and Professionalism)
Introduction: Implementing “Competency-Based Medical education” in Indian medical colleges has necessitated reengineering by the stakeholders at the institutes. Changes in the curriculum are usually inundated with challenges. The present study aimed to evaluate the implementation of the CBME curriculum for Phase II medical undergraduates in our institute.Methods: This qualitative study involved faculty members from Pathology, Microbiology, and Pharmacology teaching Phase II medical undergraduates, who participated in three focus groupdiscussions (one per department) to discuss the strategies and challenges in curriculum implementation. A gap analysis followed, with individual in-depth interviews with the departmental heads to identify solutions for the challenges. A review meeting was held with the dean, curriculum committee members, and phase II faculty members to finalize the action plan.Results: A total of 18 faculty members, predominantly females, in different age ranges (29 to 68 years) and teaching experiences (4 to 34 years) participated in this study. The faculty members have adopted various strategies for curriculum implementation such as preparing departmental planners, framing lesson plans, using interactive teaching-learning methods and e-learning, conducting self-directed learning sessions, ensuring alignment and integration, incorporating skill modules, ensuring student logbook maintenance, using appropriate assessment methods and implementing AETCOM modules. However, they faced challenges in implementing self-directed learning sessions, using e-learning platforms and recommended faculty development programs.Conclusion: Our study reveals that the paraclinical departments at our institute have taken appreciable steps in implementing the CBME curriculum for Phase II MBBS students, despite ongoing challenges. Addressing these challenges requires careful planning and evaluation, with faculty sensitization being crucial for smooth implementation. The key outcome of the study was establishing various subcommittees within the Curriculum Committee and Medical Education Unit to facilitate the implementation of various CBME components, supported by regular feedback mechanisms. Also, the action plan was shared with the Medical Education Unit to organize appropriate faculty development programs.